PARIWISATA DAN LINGKUNGAN: ANALISIS COVID-19 SECARA GLOBAL DAN PENGARUHNYA DI ASEAN - Ajeng Ramadhita Larasati; Dadang Suganda; Cipta Endyana (UHN IGB Sugriwa Denpasar, 2021)
COVID-19 is an outbreak of the virus that became a concern of citizens of the world from the end of 2019 until the time this research was made. One of the industries in the world that are most affected by the blow of the COVID-19 outbreak is tourism. This study aims to analyze tourism internationally and its impact on ASEAN countries. In the environmental sector, it is seen from the perspective of limiting tourist mobility that moves tourists globally decline, especially in ASEAN countries so that it impacts on the recovery of nature-based tourism or that promotes ecosystems. With the bibliometric study approach, this research is expected to be able to briefly answer the things that are happening in the ASEAN tourism industry. The results of this study are the visible economic impacts of the tourism sector which are quite affected by the COVID-19 pandemic. However, the environmental impact in tourism that occurs from limiting human mobility to visit is one of the beneficiaries.